A retrospective study on sickle cell disease-associated cardiovascular anomalies - Dhar, Srikant Kumar; Jafri, Asif Dabeer; Singh, Muktesh; Satale, Aniket (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Sickle cell disease (SCD), a chronic inherited hemolytic disorder prevalent in certain regions of India and globally, is associated with various cardiovascular complications that significantly impact morbidity and mortality. The objective is to assess the relationship among clinical, electrocardiographic, and echocardiographic findings in individuals diagnosed with sickle cell disease, and, as a secondary aim, to contrast these findings with those observed in patients with SCTtaking into account different age groups across both sexes. Material and methods. This study included thirty-four individuals previously diagnosed with sickle cell disease or SCTbased on hemoglobin electrophoresis. Clinical records were reviewed to obtain data from comprehensive examinations, including electrocardiographic and echocardiographic assessments. Cardiac function was evaluated, interpreted, and compared between the two groups using documented ECG and echocardiography results. Results. A total of 34 participants were enrolled, including 23 individuals with SCD and 11 with sickle cell trait (SCT). The mean age was 28.6±9.3 years in the SCD group and 30.2±8.7 years in the SCT group (p=0.57). Males predominated in both groups (SCD: 65.2%; SCT: 63.6%). Clinical examination revealed a statistically significant higher frequency of displaced apex beat in the SCD group (60.9%) compared to SCT (18.2%) (p=0.03). Electrocardiographic abnormalities such as left ventricular hypertrophy were more common in SCD (47.8%) than SCT (18.2%) (p=0.04). ST-T changes were seen in 56.5% of SCD vs. 9.1% of SCT (p=0.01). Echocardiographic findings demonstrated significantly elevated pulmonary artery systolic pressure (PASP) in the SCD group (38.6±6.2 mmHg) compared to SCT (28.4±5.7 mmHg) (p < 0.001). Mean pulmonary artery pressure (mPAP) was also higher in SCD (25.3±4.8 mmHg) vs. SCT (19.2±3.9 mmHg) (p=0.002). Tricuspid regurgitation velocity (TRV) was elevated in SCD (2.9±0.3 m/s) compared to SCT (2.4±0.2 m/s) (p=0.001). Right ventricular dilatation and diastolic dysfunction were noted in 39.1% and 34.8% of SCD cases, respectively, while absent in SCT (p<0.05 for both). In univariate logistic regression, apex beat displacement (OR=4.6; p=0.04), elevated PASP (OR=5.2; p=0.01), increased mPAP (OR=4.3; p=0.02), and TRV (OR=6.1; p=0.009) were significant predictors of SCD. Multivariate logistic regression identified PASP as an independent predictor of SCD (OR=4.8; 95% CI: 1.3‒17.9; p=0.02). Conclusion. The findings highlight that patients with sickle cell disease exhibit a significantly higher burden of cardiac abnormalities than those with sickle cell trait. Among the evaluated parameters, pulmonary artery systolic pressure emerged as an independent predictor of sickle cell disease.